ANTIDIABETIC AND ANTIOXIDANT EFFICACY OF BONE MARROW STEM CELLS ON STZE-INDUCED MALE ALBINO WISTAR RATS - JASMINENATHESHA M; S, Jenifer; RAJALAXMI M; MANIVANNAN S (Innovare Journal of Sciences, 2018)
Diabetes mellitus is a multi-metabolic disorder that influences more than 348 million people worldwide. A key goal of diabetes treatment is to prevent complications because over time, diabetes can damage the heart, blood vessels, eyes, kidneys, and nerves. Consequently there is an incredible need to develop new and successful therapies for treating diabetic complications early before it causes irreparable tissue damage. Bone marrow derived mesenchymal stem cells (BMSCs) offer significant benefits for clinical application, because they can be easily harvested and, when autologous transplanted, there is no immunological rejection. Moreover, BMSCs can differentiate into a wide variety of cell types. Here, we focused on bone marrow-derived mesenchymal stem cells (MSCs) can transdifferentiate into insulin-producing cells (IPC) under defined conditions and normalize the glucose level of streptozotocin (STZ)- induced diabetic rats.The main objective of the study was To evaluate the antidiabetic activity of the Dental pulp cells in Streptozotocin (STZ)-induced diabetic Wistar albino rats.To calculate the biochemical estimation of both normal and treated groups.To study the effects of dental pulp cells on morphological characterization of normal and treated groups. Streptozotocin.,Wistar albino rat.,Insulin.,stem cell.,fibroblast